2021
DOI: 10.1590/1806-9282.20210451
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the expression profile of vitamin D receptor and its related long non-coding RNAs in patients with acute lymphoblastic leukemia

Abstract: OBJECTIVE: Acute lymphoblastic leukemia (ALL) is the most common type of childhood cancer. Previous studies have indicated the involvement of vitamin D receptor (VDR) and related long noncoding RNAs (lncRNAs) signaling in the pathophysiology of several cancers. However, their contribution to ALL remains to be elucidated. METHODS:In this case-control study, 30 patients with newly diagnosed ALL and 30 age-and sex-matched healthy children were selected.Then, the level of 25(OH) vitamin D and the expression of VDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Then PBMCs were isolated using Ficoll density gradient centrifugation. After washing the PBMCs twice with phosphate-buffered saline solution, total RNA was extracted using Trizol (GeneAll, South Korea) (18). Subsequently, cDNA was synthesized from the extracted total RNAs using the cDNA synthesis kit (Parstous, Iran).…”
Section: Sample Collection and Rna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then PBMCs were isolated using Ficoll density gradient centrifugation. After washing the PBMCs twice with phosphate-buffered saline solution, total RNA was extracted using Trizol (GeneAll, South Korea) (18). Subsequently, cDNA was synthesized from the extracted total RNAs using the cDNA synthesis kit (Parstous, Iran).…”
Section: Sample Collection and Rna Extractionmentioning
confidence: 99%
“…All reactions were carried out in duplicate using the Mic PCR system (BMS, Australia). The temperature profi le of PCR reactions was as follows: 95 °C for 15 min, followed by 40 cycles including 95 °C for 40 s, 62 °C for 25 s, and 72 °C for 15 s (18,19).…”
Section: Quantitative Real-time Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…For instance, the ER shows elevated expression in oral cancer, while its expression varies in lung cancer [ 50 , 51 ]. Similarly, VDR exhibits diminished expression in HM but presents differential expression in esophageal cancer [ 38 , 59 , 60 ]. Additionally, distinct isotypes of specific NRs, like PPAR, have unique functional implications.…”
Section: Nrs In Hmmentioning
confidence: 99%
“…The intracellular receptor, VDR, upon binding with its active metabolite 1,25(OH)2D, becomes the focal point for the transcriptional modulation of numerous target genes [ 229 , 232 ]. Multiple studies have reported the downregulation of VDR expression in HM [ 59 , 60 ].…”
Section: Nrs In Hmmentioning
confidence: 99%